P20 Does Kaftrio® reduce IV antibiotic burden in cystic fibrosis? A retrospective observational evaluation. Issue 5 (19th April 2023) - Kafka, Susan
Abstract : Aim: Respiratory failure remains the most common cause of death in Cystic Fibrosis (CF) with chronic/complex infection a significant contributory factor. Infection frequency and associated treatment burden increase the risk drug-resistant organisms; however, stewardship strategies are challenging to translate to CF care. The CFTR modulator Kaftrio® (elexacaftor/tezacaftor/ivacaftor) launched in the UK in August 2020. Initial phase 3 clinical trials 1 2 and a subsequent open-label extension study 3 demonstrated promising data on health-related quality of life, including reduced pulmonary exacerbation (PEx) rates (63%), hospitalisation (71%) and PEx requiring IV antibiotics (78%). This evaluation aimed to provide a 'real-world' review of the impact of Kaftrio® on IV antibiotic burden (admission rates, 'bed-days', bed-day cost, total IV antibiotic use and 'AWaRE' antibiotic use) in CF patients aged 12–16 years at a single tertiary centre. Method: A single-centre retrospective observational evaluation was conducted. All 12–16 year olds on Kaftrio® were identified using the local CF database. For each patient: month/year Kaftrio® commenced and prior CFTR modulator therapy were determined. Clinical trial patients were excluded. Digital clinical information systems were used to identify 'chest-related' admissions for IV antibiotics in the 24 months prior to starting Kaftrio® and the treatment period post, up to June 2022. For each admission, drugs, doses administered and 'IV antibiotic bed-days' were determined. 'Bed-day' costs were calculated and use of 'Restricted' or 'Watch' antibiotics (WHO AWaRE/local Policy) were identified. IV antibiotic burden pre- and post Kaftrio® was evaluated. Results: 44 admissions in 33 patients were identified prior to Kaftrio®, compared with 13 admissions post-Kaftrio®, demonstrating a 65–70% overall reduction in admissions (PEx: rate 66/100patient/year vs 23/100patient/year). Pre-Kaftrio® 639 'bed days'/24 months were directly attributed to delivery of IV antibiotics-a total estimated cost of £383, 400 (estimate £600/day/medical bed). From October 2020-June 2022, the number of IV antibiotic 'bed days' fell to 183. A total reduction of 71%, with an estimated cost saving of £273, 600. In the 24 months prior to Kaftrio® a total 2849 doses of IV antibiotics were administered vs 657 doses in the same patient cohort in the period post-Kaftrio® to June 2022, an absolute reduction of 2192 doses (77%). Of the 2849 IV antibiotics pre-Kaftrio® doses, 84% were restricted/watch antibiotics (R=706; W= 1681). Usage dropped by 37.5% and 89% respectively post-Kaftrio®. Conclusion: Results suggest Kaftrio® reduces overall IV antibiotic burden in CF patients, providing real-word data supporting the phase 3 study outcomes. Significant reductions in PEx rates, IV antibiotic use, 'bed days' and associated costs were all observed. Data demonstrated an absolute reduction in the use of 'AWaRE' antibiotics, although use still accounts for a high overall proportion in this cohort. Results are limited by the data periods. Potential impact of the COVID-19 pandemic on PEx rates ('shielding' population) should be considered. Nonetheless, the significance of these findings on overall outcomes and stewardship should not be downplayed. Ongoing review, including expanded patient populations (adults; 6–11 years) is essential. Further works looking at oral antibiotics use, epidemiology, genotype and previous CFTR treatment would support extended evaluation of the overall impact of Kaftrio® on infection management in CF. References: Middleton PG, Mall MA, Drevineck P, et al . Elexacaftor-tezacaftor-ivacaftor for Cystic Fibrosis with a single Phe508del Allele. New England Journal of Medicine 2019;381 :1809–1819. Southern K, Murphy J, Sinha I, et al . Corrector therapies (with or without potentiators) for people with cystic fibrosis with class II CFTR gene variants. Cochrane Database of Systematic Review 2020;12 ;1–313. Griese M, Costa, S, Linnemann R, et al . Safety and efficacy of Elexacaftor/Tezacaftor/Ivacaftor for 24 weeks or longer in people with cystic fibrosis and one or more F598del Allele: Interim Results of an Open-Label Phase 3 Clinical Trial. American Journal of Respiratory and Critical Medicine 2021;203 ;381–384.